Elementary teachers’ digital competence and technology-based learning innovation: A case study of early artificial intelligence use in an Indonesian primary school (Diniyah: Jurnal Pendidikan Dasar, 2026)
Elementary teachers’ digital competence is increasingly important for designing responsive, engaging, and innovation-oriented learning in contemporary classrooms. This study explored how elementary school teachers’ digital competence supports learning innovation at SD Aisyiyah 1 Mataram, with attention to technology use in planning, implementation, evaluation, early Artificial Intelligence use, and contextual supporting and inhibiting factors. Using a qualitative case study design, data were collected through classroom observations, semi-structured interviews with teachers and the principal/curriculum coordinator, student open-response questionnaires, and document analysis. The findings show that teachers used digital technology mainly through PowerPoint, videos, projectors, online resources, simple digital quizzes, and AI-assisted preparation. These practices increased student attention, participation, and visual understanding, particularly when integrated with discussion and simple project-based activities. However, technology integration remained at an early stage due to limited facilities, unstable internet access, unequal teacher competence, restricted student device access, and administrative workload. The study highlights the need for sustained professional development that integrates digital pedagogy, AI literacy, collaborative learning, and school-level support. Keywords: Artificial Intelligence; digital competence; digital pedagogy; elementary school teachers; learning innovation; primary education; technology integration